Meccanica dei fluidi e fisica matematica tra ricerca e insegnamento L'opera di Antonio Melis - Borghero, Francesco; Demontis, Francesco; Polo, Maria (UNICApress, 2023)
This volume collects the publications of Prof. Antonio Melis, Dean of the Department of Mathematics and Computer Science, on the occasion of his 93rd birthday. The anastatic reprint of the papers, which cover the period from 1955 to 1999, is part of the series of other publications that UNICApress has promoted for the 400th anniversary from the founding of the University of Cagliari. Research in the field of Mathematical Physics and the teaching of Rational Mechanics at the Faculties of Sciences and Engineering are where Professor Melis' passion for Mathematics and teaching came to life.